2015
DOI: 10.1111/ejn.12881
|View full text |Cite
|
Sign up to set email alerts
|

Increased peak gamma frequency in individuals with higher levels of autistic traits

Abstract: Individual differences in orientation discrimination threshold are related to both visually‐induced peak gamma frequency and the presence of autistic traits. The relationship between peak gamma frequency and orientation discrimination thresholds may be due to both of these factors being mediated by levels of neural inhibition. No study has previously measured the relationship between peak gamma frequency and levels of autistic traits. Thus, this was the aim of the present study. We measured orientation discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 43 publications
3
40
1
Order By: Relevance
“…The frequency of gamma oscillations has been previously related to differences in behavioral performance [Dickinson et al, 2015; Edden et al, 2009], and in cognitive traits of possible clinical relevance [Dickinson et al, 2015; Kahlbrock et al, 2012]. For example, a recent study showed that the normal velocity‐dependent modulation of visual gamma frequency appeared to be impaired in children with autism spectrum disorders [Stroganova et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of gamma oscillations has been previously related to differences in behavioral performance [Dickinson et al, 2015; Edden et al, 2009], and in cognitive traits of possible clinical relevance [Dickinson et al, 2015; Kahlbrock et al, 2012]. For example, a recent study showed that the normal velocity‐dependent modulation of visual gamma frequency appeared to be impaired in children with autism spectrum disorders [Stroganova et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Across individuals, peak gamma frequency correlates with psychophysical performance in visual discrimination tasks [Dickinson et al, 2015; Edden et al, 2009]. Inter‐individual differences in frequency appear to be strongly genetically determined [van Pelt et al, 2012], though the individual peak frequency decreases with age [Gaetz et al, 2012; Muthukumaraswamy et al, 2010; Robson et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…This task was adapted from Edden and colleagues ), and was used by us in previous work (Dickinson et al 2014;Dickinson et al 2015). The task design is illustrated in Figure 1.…”
Section: Orientation Discrimination Taskmentioning
confidence: 99%
“…Stimuli were identical to those that we previously used to measure peak gamma frequency (Dickinson et al 2015) and were originally adapted from Edden and colleagues ). A red cross (1° x 1°) was present in the centre of the screen throughout the experiment and participants were asked to fixate on this cross throughout Each trial consisted of a black and white square grating (4° x 4°; spatial frequency 3 cycles/degree; contrast 99.6%; mean luminance 39.33 cd/m2) presented to the bottom left of the fixation point.…”
Section: Eeg Taskmentioning
confidence: 99%
“…In particular, gamma activity has on the one hand been used to characterize functional connectivity in cortical networks, for example, [Cabral et al, 2011] and on the other to study aberrant dynamics associated with potential pathophysiology. Gamma oscillations show a strong genetic dependency and may play an important role in disclosing aberrant neuronal processing in psychiatric diseases [Uhlhaas and Singer, 2012; van Pelt et al, 2012], such as autism [Dickinson et al, 2015] and schizophrenia [Gonzalez‐Burgos and Lewis, 2008]. They are thought to arise from a coordinated balance between cortical excitation and inhibition [Başar et al, 2015; Buzsáki and Wang, 2012] and are implicated a variety of cognitive processes like working memory [Miller and Wilson, 2008; Pesaran et al, 2002; Siegel et al, 2009] and visual attention [Womelsdorf et al, 2006].…”
Section: Introductionmentioning
confidence: 99%